Human herpesvirus 6 U94 suppresses tumor cell proliferation and invasion by inhibiting Akt/GSK3β signaling in glioma - Jiang, Wenqing; Li, Lingyun; Tang, Huamin; Gu, Bin; Feng, Dongju; Zhou, Feng; Liu, Yingxia; Xu, Xianyi; Chen, Yun; Yao, Kun; Hu, Weixing (Translational Cancer Research, 2018)
Background: Glioma is a highly malignant brain tumor with limited therapeutic options. We reported previously that the DNA and protein of human herpesvirus 6 (HHV-6) could be detected in glioma tumor tissues. However, the effects of HHV-6 U94, which is abundantly expressed during the virus’ latency period, on glioma progression remain unknown. In the present study, we aimed to determine on the roles of HHV-6 U94 in glioma progression. Methods: The ectopic expression of U94 in glioma U87 cells was achieved using lentivirus infection. The effects of HHV-6 U94 on cell proliferation, migration, and invasion were examined using cell counting kit-8 (CCK-8), colony formation, wound healing, Transwell migration, and invasion assays. The gene expression profiles of U94-expressing U87 cells were analyzed using microarray analysis and confirmed by quantitative RT-PCR and western blotting analysis. The effects of HHV-6 U94 on glioma tumor growth were evaluated using a xenograft nude mouse model. Results: We found that ectopic expression of U94 in glioma U87 cells dramatically inhibited colony formation and cell proliferation in vitro, and suppressed xenograft tumorigenesis in glioma-bearing nude mice. In addition, overexpression of U94 suppressed the migration and invasion of glioma U87 cells. Furthermore, enhanced expression of U94 in glioma cells downregulated ras-related protein rap-1A (RAP1A), solute carrier family 7 member 11 (SLC7A11), forkhead box P1 (FOXP1), and transcription factor 4 (TCF4) expression by inhibiting Akt kinase (AKT/glycogen synthase kinase 3 beta (GSK3β) signaling, which proteins are associated with the malignant phenotypes of glioma cells. Conclusions: Taken together, these data indicated that HHV-6 U94 could suppress tumor cell proliferation and invasion by inhibiting AKT/GSK3β signaling in glioma.